2022
DOI: 10.5334/bc.254
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and opportunities of fast-growing biobased material use in buildings

Abstract: Limiting global warming to 1.5°C requires immediate and drastic reductions in greenhouse gas (GHG) emissions. A significant contributor to anthropogenic global GHG emissions is the production of building materials. Biobased materials offer the potential to reduce such emissions and could be deployed in the short term. Timber construction has received the main attention from policy and industry. However, the implementation of timber construction at the global scale is constrained by the availability of sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Non-timber lignocellulosic materials generated from forestry, agriculture and biomass residue streams represent key local building material solutions. Current models of bamboo and straw, two fast-growing renewable biomass resources, show that annual supply outweighs demand (Göswein et al 2022). Each year, an estimated 140 gigatons of by-product biomass is generated worldwide (Tripathi et al 2019).…”
Section: Supplies Of Biomass Residues Outweigh Current and Projected ...mentioning
confidence: 99%
“…Non-timber lignocellulosic materials generated from forestry, agriculture and biomass residue streams represent key local building material solutions. Current models of bamboo and straw, two fast-growing renewable biomass resources, show that annual supply outweighs demand (Göswein et al 2022). Each year, an estimated 140 gigatons of by-product biomass is generated worldwide (Tripathi et al 2019).…”
Section: Supplies Of Biomass Residues Outweigh Current and Projected ...mentioning
confidence: 99%
“…Today, architects have a plethora of opportunities to replace non-renewable, energy and carbon-intensive construction materials with biogenic or biobased materials, which reduce the environmental footprint and potential health risks of conventional construction materials in buildings (Göswein et al 2022). In addition to traditional building materials, such as wood, straw, and hemp, much research has been conducted on how to industrially cultivate, breed, farm, and grow biogenic construction materials (Hebel and Heisel 2017) and how to successfully integrate them in construction details, wall sections, and building designs (Lewis et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…and sanitation (SDG 6) [1]. Through a conceptual framework of building materials, Omer and Noguchi [2] concluded that building materials can help achieve 13 goals, namely SDGs 1,3,4,6,7,8,9,11,12,13,14,15 and 17,and 25 targets of the UN 2030 Agenda. The authors provided a state-of-the-art review of the SDGs, focusing on the connections to buildings and materials.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the emissions from manufacturing and use, carbon-storing materials offer a significant advantage that might be the key point for future post-carbon construction. Using fast-growing bio-based materials for construction products can create carbon-neutral or even carbon-negative products [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation